Modelo de custos ambientais aplicado à gestão e destinação de resíduos - Segatto, Sara Schafer (2012)
Environmental issues have been widely discussed in the contemporary world and particularly in the business community. But how to measure the costs related to the environment is still an issue with some indefinitions and controversy. The informational needs of managers are focused on the choice of proposals that provide qualitative data about the problems, combined with quantitative data. Some authors have created models to measure these costs, however, they have not widely accepted because they are not comprehensive or because they have little explanatory calculation methodology. On this basis, the aim of this work was proposed a model of environmental costs. For this purpose, it was analyzed the main existing models, developed the Model of Environmental Costs Applied to the Destination of Waste using tools such as GUT and Material Balance, aimed at determining the most critical routes and, after, applied in the sector of Hygiene and Cleaning Services (SHL), University Hospital of Santa Maria (HUSM). For this, the methodology used was applied research, with qualitative approach, exploratory as to the aims and field research to validate. The application of the proposed model to the sector showed that initially there are at least twenty-four alternatives to analyze the costs, however, after application of the model, it was obtained only three alternatives for study. This significant decrease in the number of alternatives resulted in cost savings for both the analysis of every possible treatment of waste and for the costs associated with technological studies to enable each alternative identified. The proposed model when compared to existing, proved to be more dynamic and easy to use, besides to help in the identification of environmental impacts caused by products.